Towards low-emission food systems in Ghana: A country profile - Pingault, N.; Martius, C. (CIFOR-ICRAF, 2025)
Food systems – spanning the five economic sectors of agriculture, land use, land use change and forestry (LULUCF), energy, industrial processes and product use (IPPU), and waste – account for about one-third of global anthropogenic greenhouse gas emissions, making them a critical yet often under-reported component of the climate challenge. This document is part of a series of national country profiles. Comparing FAOSTAT and national estimates from Ghana’s first Biennial Transparency Report (BTR) and Common Reporting Tables (CRT), this document provides an overall view of land use, forest, and agriculture, food security and diet, and food system emissions in Ghana. It identifies the following no-regret priorities for mitigation action: (i) zero-deforestation cocoa agroforestry that combines yield intensification with forest conservation and smallholder compliance with the EU Deforestation Regulation; (ii) savanna fire management through early burning and community firebreaks to curb late-season fires and emission peaks; (iii) livestock productivity and manure management improvements focusing on feed quality, animal health and composting to lower methane and nitrous oxide intensities without harming food security; (iv) urban wastewater and solid waste management via segregation, composting and anaerobic digestion to reduce methane and to recycle nutrients; and (v) nutrition-sensitive diversification through aquaculture, legumes and poultry to close the protein supply gap while cutting emissions intensity.